Guide for Psychology Majors: A Student Handbook. - Flannelly, Linda (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

Revision of an Interactive Computer Program. - Harmon, Duane (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

(MMPI and Rorschach) - Muller, Bruce (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

Behavior Modification - Sherman, William M. (Harper & Row, 1990)
Keywords: Behavior modification; dept.psy; faculty_collection

Choice behavior in transition: development of preference for the higher probability of reinforcement - Bailey, John T.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 1990)
Ten acquisition curves were obtained from each of 4 pigeons in a two‐choice discrete‐trial procedure. In each of these 10 conditions, the two response keys initially had equal probabilities of reinforcement, and subjects' choice responses were about equally divided between the two keys. Then the reinforcement probabilities were changed so that one key had a higher probability of reinforcement (the left key in half of the conditions and the right key in the other half), and in nearly every case the subjects developed a preference for this key. The rate of acquisition of preference for this key was faster when the ratio of the two reinforcement probabilities was higher. For instance, acquisition of preference was faster in conditions with reinforcement probabilities of .12 and .02 than in conditions with reinforcement probabilities of .40 and .30, even though the pairs of probabilities differed by .10 in both cases. These results were used to evaluate the predictions of some theories of transitional behavior in choice situations. A trial‐by‐trial analysis of individual responses and reinforcers suggested that reinforcement had both short‐term and long‐term effects on choice. The short‐term effect was an increased probability of returning to the same key on the one or two trials following a reinforcer. The long‐term effect was a gradual increase in the proportion of responses on the key with the higher probability of reinforcement, an increase that usually continued for several hundred trials. 1990 Society for the Experimental Analysis of Behavior
Keywords: Animal; Attention; Choice Behavior; Color Perception; Discrimination Learning; Motivation; Orientation; Pigeons; Probability Learning; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; acquisition; animal; article; attention; choice; color vision; decision making; dept.psy; discrimination learning; key peck; learning; motivation; orientation; pigeon; pigeons; probability of reinforcement; reinforcement

Differences across gender, grade level, and academic track in the content of the ideal self-image - Bybee, Jane; Glick, Marion; Zigler, Edward (Sex Roles, 1990)
Students from the 5th, 8th, and 11th grades (55 male and 53 female) were asked to describe their ideal self-image. Analyses revealed a number of gender and developmental differences not found with other self-image measures. A greater proportion of females than males mentioned two of the categories related to family life: marriage and improving relations with their family of origin. Mentions of categories surrounding athletics were more prevalent among males. Grade level differences in the content of the ideal self-image reflected cognitive-developmental shifts away from concrete descriptors, changes in physical maturity and the heightened importance of peer relationships around adolescence, and the approach of developmental milestones. Fewer students mentioned physical appearance at higher grade levels. Mentions of athletic abilities and social acceptance peaked at the 8th grade, while mentions of college, marriage, and having children rose at higher grade levels. Differences in the content areas mentioned by average versus advanced track students appeared to reflect differences in both cognitive-developmental level and socialization experiences. © 1990 Plenum Publishing Corporation.
Keywords: dept.psy

Choice between delayed reinforcers and fixed‐ratio schedules requiring forceful responding - Mazur, James E; Kralik, J D (Journal of the Experimental Analysis of Behavior, 1990)
This experiment measured pigeons' choices between delayed reinforcers and fixed‐ratio schedules in which a force of approximately 0.48 N was needed to operate the response key. In ratio‐delay conditions, subjects chose between a fixed‐ratio schedule and an adjusting delay. The delay was increased or decreased several times a session in order to estimate an indifference point—a delay duration at which the two alternatives were chosen about equally often. Each ratio‐delay condition was followed by a delay‐delay condition in which subjects chose between the adjusting delay and a variable‐time schedule, with the components of this schedule selected to match the ratio completion times of the preceding ratio‐delay condition. The adjusting delays at the indifference point were longer when the alternative was a fixed‐ratio schedule than when it was a matched variable‐time schedule, which indicated a preference for the matched variable‐time schedules over the fixed‐ratio schedules. This preference increased in a nonlinear manner with increasing ratio size. This nonlinearity was inconsistent with a theory that states that indifference points for both time and ratio schedules can be predicted by multiplying the choice response‐reinforcer intervals of the two types of schedules by different multiplicative constants. Two other theories, which predict nonlinear increases in preference for the matched variable‐time schedules, are discussed. 1990 Society for the Experimental Analysis of Behavior
Keywords: Animal; Choice Behavior; Conditioning, Classical; Exertion; Memory; Mental Recall; Motivation; Pigeons; Psychomotor Performance; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; adjusting procedure; animal; article; conditioned reflex; decision making; dept.psy; exercise; fixed ratio; key peck; memory; motivation; pigeon; pigeons; psychomotor performance; recall; reinforcement; reinforcer delay; response effort; variable time